2021
DOI: 10.1111/cpr.13095
|View full text |Cite
|
Sign up to set email alerts
|

Scara3 regulates bone marrow mesenchymal stem cell fate switch between osteoblasts and adipocytes by promoting Foxo1

Abstract: Objectives Scavenger receptor class A, member 3 (Scara3) was involved in adipogenesis. However, the effect of Scara3 on the switch between osteogenesis and adipogenesis of bone marrow mesenchymal stem cells (BMSCs) remains elusive. Materials and Methods The correlations between SCARA3 with the osteogenic‐related were analysed based on the GTEx database. The effects of Scara3 on osteogenic or adipogenic differentiation of BMSCs were evaluated by qPCR, Western blot (WB) and cell staining. The mechanisms of Scara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 48 publications
(130 reference statements)
1
16
0
Order By: Relevance
“…38 In OP, it is reported that SCARA3 expression is upregulated during the osteogenesis of hBMSCs and promotes the osteogenic differentiation of hBMSCs by regulating Foxo1 while inhibiting adipogenic differentiation. 39 Our study also found that SCARA3 expression was significantly upregulated in hBMSCs induced by osteogenic differentiation, that additionally, SCARA3 was proven to be a downstream target of miR-210-3p, and that MOP could upregulate SCARA3 expression through repressing miR-210-3p expression.…”
Section: Discussionsupporting
confidence: 73%
“…38 In OP, it is reported that SCARA3 expression is upregulated during the osteogenesis of hBMSCs and promotes the osteogenic differentiation of hBMSCs by regulating Foxo1 while inhibiting adipogenic differentiation. 39 Our study also found that SCARA3 expression was significantly upregulated in hBMSCs induced by osteogenic differentiation, that additionally, SCARA3 was proven to be a downstream target of miR-210-3p, and that MOP could upregulate SCARA3 expression through repressing miR-210-3p expression.…”
Section: Discussionsupporting
confidence: 73%
“…From the bioinformatics analysis, we obtained 57 OP-related target genes of hsa-miR-296-5p, hsa-miR-370, and hsa-miR-635, including fibroblast growth factor receptor 1 (FGFR1), [39] RUNX2, [40] FOXO1, [41] STAT3 [42] and recombinant gremlin 2 (GREM2), [43] all of which have been confirmed to be the key ones. According to the functional enrichment analysis on the related genes predicted by hsa-miR-370, PI3K-alpha (PIK3CA), FOXO1, STAT3 and mitogen-activated protein kinase 8 (MAPK8) were enriched in FoxO signaling pathway and advanced glycosylation end product (AGE) and receptor of advanced glycosylation end product (RAGE) signaling pathway, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…reported a positive association between Scara3 and osteogenic differentiation of BM-MSCs. 23 Nevertheless, biomarkers of osteogenic differentiation are still limited.…”
Section: Discussionmentioning
confidence: 99%